The Correlation Between Type and Stage of Lung Cancer with The Chronic Obstructive Pulmonary Disease Group at Arifin Achmad Hospital, Pekanbaru - Gurning, Andi Sarikawan; Munir, Sri Melati; Yunus, Faisal; Fauzi, Zarfiardy Aksa; Adrianison, Adrianison; Yovi, Indra; Indriani, Sri Indah (Jurnal Respirologi Indonesia, 2025)
Background: The relationship between lung cancer (LC) and chronic obstructive pulmonary disease (COPD) has been extensively studied but is still up for debate. COPD is a molecularly based illness and one of the independent risk factors for lung cancer, particularly squamous cell carcinoma. This study uses spirometry to assess the relationship between the type and stage of LC and COPD in a group of LC patients at Arifin Achmad Hospital. Methods: This cross-sectional study was conducted on lung cancer patients in Arifin Achmad Hospital, Pekanbaru, from June 2022 to December 2022. Based on spirometry examination, patients were grouped according to the degree of COPD. Then, the relationship between the COPD group and the type and degree of cancer was determined. Results: The study involved 52 patients predominantly male (71.2%), aged over 40 years (92.3%), Smokers and former smokers with Severe Brinkman index (69.2%), restrictive lung function (34.6%), COPD group D (40.4%), adenocarcinoma (61.5%), stage IV lung cancer (92,3%) and WHO Performance Status Scale 2 (61.5%). The FEV1/FVC rate in this study was 66.67%. There is a link between the stage of lung cancer and the group of COPD (P=0.001). Conclusion: There is a relation between the stage of LC in the COPD group, which is predominantly with stage IV lung cancer, and group D of COPD.